2020
DOI: 10.1016/s2214-109x(20)30116-9
|View full text |Cite
|
Sign up to set email alerts
|

Considering inequalities in the school closure response to COVID-19

Abstract: Considering inequalities in the school closure response to COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
256
1
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(287 citation statements)
references
References 2 publications
(2 reference statements)
2
256
1
18
Order By: Relevance
“…However, other inequalities have also been noted such as in educational opportunities for children during school closures. 26 These remain to be explored further in future studies. Finally, our study used two different SEP indices and further tested specific aspects of SEP in sensitivity analyses, but we restricted measurement of SEP to a finite list of factors.…”
Section: Discussionmentioning
confidence: 97%
“…However, other inequalities have also been noted such as in educational opportunities for children during school closures. 26 These remain to be explored further in future studies. Finally, our study used two different SEP indices and further tested specific aspects of SEP in sensitivity analyses, but we restricted measurement of SEP to a finite list of factors.…”
Section: Discussionmentioning
confidence: 97%
“…Many countries have implemented the school closure policy as an immediate response to the COVID-19 outbreak to reduce social contact [ 1 ]. The effectiveness of school closures on the spread of the coronavirus remains unknown [ 5 ], yet the adverse consequences of school closures on children’s growth and development started to appear soon afterward [ 6 , 7 , 8 ]. Recent studies showed that children have fewer regular eating and sleeping patterns, longer screen time, fewer physical activities, increased stress, and less social interaction during school closures, which pose risk to their physical and mental health [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, mental health of children and adolescents undergoes a sudden stress test during school closure, with increased risk of loneliness, addiction to videogames and binge watching, alteration of circadian rhythms, direct or assisted domestic violence, and academic achievement gaps. Especially for the latter, inequalities related to socioeconomic status and differences related to pre-existing vulnerabilities will be further amplified [2][3][4].…”
Section: To the Editormentioning
confidence: 99%
“…Instead, considering how much social isolation may affect mental health of children and adolescents [2][3][4], we strongly suggest that medical, educational and economical authorities should implement as soon as possible strategic plans for a progressive re-start of school or educational activities. This re-start should ensure a calculated trade-off between risk of COVID-19 infection and reduction of risk for children's well-being, especially for more vulnerable subgroups, as those of families with low socioeconomic status and those with pre-existing mental health problems or learning difficulties.…”
Section: To the Editormentioning
confidence: 99%